Advancing sustainability in the steel industry: the key role of the triple helix sectors - da Rocha, Aglaé Baptista Torres [UNESP] (2024)
The steel industry, crucial to the global economy, grapples with critical sustainable challenges, including high energy consumption, greenhouse gas emissions, and non-renewable resource utilization, making sustainability imperative for upholding its economic role without compromising the planet or societal well-being. This study proposes a framework aimed at advancing sustainability in the steel industry through the articulation of the triple helix sectors (university, industry, and government). Based on the integrative review scientific method, systematic selection, interpretation, and synthesis of information from various sources were carried out to map a technical-scientific scenario of sustainability in the steel industry. This scenario informed benchmarking which, in light of the scientific theory and the authors’ expertise, enabled the proposition of customized actions aimed at the triple helix actors. The main theoretical-scientific contribution lies in deepening and expanding the knowledge that connects sustainability to the steel industry, thus reinforcing the basis for future research and empirical studies. As for the managerial-applied contribution, this work can guide universities in developing sustainable projects and establishing industrial partnerships; steel companies benefit from the best practices and technologies, while also achieving regulatory compliance; and governments can promote public policies that boost sustainability in the steel sector.